RETRACTED: The importance of agricultural clusters for the development of rural regions - Yekimov Sergey; Kontsevaya Stanislava; Poltorak Anastasiya S.; Sharin Oleksandr; Verkhovod Iryna; Kuris Yurii (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 538, 00001 (2024), https://doi.org/10.1051/e3sconf/202453800001